2013
DOI: 10.1111/cea.12054
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study of body mass index in 23 000 individuals with and without asthma

Abstract: Background Both asthma and obesity are complex disorders that are influenced by environmental and genetic factors. Shared genetic factors between asthma and obesity have been proposed to partly explain epidemiological findings of co-morbidity between these conditions. Objective To identify genetic variants that are associated with body mass index (BMI) in asthmatic children and adults, and to evaluate if there are differences between the genetics of BMI in asthmatics and healthy individuals. Methods In tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 57 publications
(71 reference statements)
0
45
0
3
Order By: Relevance
“…Such findings underscore the importance of studying multiple racial and ethnic groups in genetic association studies. To our knowledge, studies of pleiotropy between asthma and obesity genetics have only been performed in pediatric populations of European descent (Gonzalez et al 2014; Melen et al 2013; Melen et al 2010; Wang et al 2015). This presents a gap in our scientific knowledge that limits the standard of care available for populations, such as African Americans, who are among the most severely affected by the co-occurrence of these conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such findings underscore the importance of studying multiple racial and ethnic groups in genetic association studies. To our knowledge, studies of pleiotropy between asthma and obesity genetics have only been performed in pediatric populations of European descent (Gonzalez et al 2014; Melen et al 2013; Melen et al 2010; Wang et al 2015). This presents a gap in our scientific knowledge that limits the standard of care available for populations, such as African Americans, who are among the most severely affected by the co-occurrence of these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic associations with asthma may potentially be mediated by obesity status. Pleiotropic effects between obesity and asthma at the single nucleotide polymorphism (SNP) or gene-level may partly explain the association between these two conditions (Gonzalez et al 2014; Melen et al 2013; Melen et al 2010; Wang et al 2015). The majority of asthma genetic studies have not explored whether obesity mediates the association between identified genetic variants and asthma status (Akhabir and Sandford 2011; Hoffjan et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, while genetic analysis did not reveal any association for these genes, together with no association for ADRB2, and with the comorbidity of asthma and obesity, a trend was observed for glucosamine-6-phosphate deaminase-2 (GNPDA2), protein tyrosine phosphatise, receptor type D (PTPRD), and roundabout axon guidance receptor homolog 1 (ROBO1), although further research is likely required. In a recent study by Melén et al, 68 the DENN/MAD domain containing 1B (DENND1B), which is a protein that may play a role in clathrin-mediated endocytosis, was identified as being associated with BMI in asthmatic children, while no such relation was revealed for ADRB2. In another study (Tesse et al), the authors suggested that the TNFA and VDR genes probably could be involved in pleiotropic mechanisms responsible for the comorbidity of asthma and some endocrine disorders.…”
Section: Shared Genetic Factors For Asthma and Obesitymentioning
confidence: 99%
“…Various pathways have been proposed, including mechanical changes from excessive weight (8); existence of comorbidities, such as obstructive sleep apnea; a proinflammatory milieu that exists in obesity; and shared genetic polymorphisms (9,10). It is becoming progressively clear that the "obese asthmatic" phenotype is likely complex and multifactorial.…”
mentioning
confidence: 99%